Effect of Enamel Bleaching on the Bond Strength of Ceramic-A Systematic Review - Tsz Ho Seto; Anastasiia Grymak; Vidya Mudliar; Joanne Jung Eun Choi (MDPI AG, 2022)
The increase in aesthetic demands has increased the use of ceramic dental restorations in dentistry. Ceramic restorations are bonded to the tooth structure using adhesives. There is a lack of standard guidelines in terms of post-bleaching time intervals and bond strengths of ceramic restorations. Bleaching products have also been stated to affect the morphology of enamel. Therefore, the purpose of this systematic review is to evaluate the bond strength between ceramic and enamel and the changes in the surface roughness of enamel post teeth bleaching. An electronic search was performed in the databases PubMed, OVID MEDLINE, Scopus, and Web of Science with MESH terms: "adhesion OR bonding", "ceramic OR ceramics OR dental porcelain", "tooth bleaching OR teeth bleaching OR tooth whitening OR teeth whitening" and "enamel OR dental enamel OR enamels OR dental enamels". The articles were screened, and the final selection of articles was obtained by using the inclusion and exclusion criteria. Of the 170 studies identified from the search, only 12 studies met the inclusion criteria and were selected for full-text review. A further search by hand was performed, and additional 48 studies were selected. From the 60 full-text studies, 18 studies met the inclusion criteria and were included for data extraction. The results were based on a descriptive analysis of the effect on bond strength of ceramic to enamel after a bleaching protocol and the changes in the surface roughness of enamel post bleaching protocol. In conclusion, bleaching protocols alter the surface roughness of enamel and, thus, the shear bond strength between ceramic and enamel. Bleaching treatments with a higher concentration of hydrogen peroxide reduce the bond strength between ceramic and enamel. Delaying bonding after bleaching for up to 7 days increases the bond strength between ceramic and enamel.